The effects of stem cells on burn wounds: a review - Francis, Eamon (Int J Burns Trauma, 2019)
Introduction: Stem cell therapy application is at the vanguard of regenerative medicine across all medical disciplines. Stem cells are of special interest in burn wounds, as they have multiple potential indications for application; including - accelerating wound healing, improving skin regeneration to incorporate skin appendages, reducing fibrosis and improving scarring. Methods: A literature review was performed using both MeSH and keyword searches of PubMed to identify all potentially suitable publications. Search criteria were restricted to the English language, but acceptable English translations were sought for inclusion. Inclusion dates were from 2003 up until and including 2017. Studies included looked at stem cells in burn wounds only. Results: There were 692 potentially suitable publications of which 72 were included for review. These included a systematic reviews and original research articles. Conclusions: Stem cells accelerate burn wound healing by inducing neo-angiogenesis, collagen deposition and granulation tissue formation. They modulate the inflammatory response and reduce the risk of infection. They can regenerate skin appendages and halt he zone of stasis in acute burn injury. However with these pre-clinical animal model studies we must be cautious with our interpretation of this novel therapy.